2005
DOI: 10.2214/ajr.184.4.01841266
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of FDG PET and SPECT for Detection of Bone Metastases in Breast Cancer

Abstract: Bone SPECT is superior to FDG PET in detecting bone metastases in breast cancer. The sensitivity of osteoblastic lesions is limited with FDG PET. Surveillance of metastatic spread to the skeleton in breast cancer patients based on FDG PET alone is not possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
55
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(58 citation statements)
references
References 12 publications
1
55
0
2
Order By: Relevance
“…The clinical guidelines on use of radionuclides from the American College of Cardiology and the American Heart Association [15] report that average sensitivity is 87% for detecting angiographically significant coronary artery disease, while average specificity is 73%. [16], a lesion-by-lesion analysis in 15 patients showed that SPECT was more sensitive (85%) compared to PET (17%) and the overall accuracy of SPECT was higher (96%) compared to PET (85%).…”
Section: Cardiology Pet Vs Spectmentioning
confidence: 97%
“…The clinical guidelines on use of radionuclides from the American College of Cardiology and the American Heart Association [15] report that average sensitivity is 87% for detecting angiographically significant coronary artery disease, while average specificity is 73%. [16], a lesion-by-lesion analysis in 15 patients showed that SPECT was more sensitive (85%) compared to PET (17%) and the overall accuracy of SPECT was higher (96%) compared to PET (85%).…”
Section: Cardiology Pet Vs Spectmentioning
confidence: 97%
“…Further gains in sensitivity and, especially, in specificity and diagnostic confidence were apparent with SPECT/CT (22)(23)(24)(25) because of the greater contrast resolution of SPECT coupled with the ability to reduce false-positive diagnoses of metastases through correlation with the morphologic appearance of lesions on CT.…”
Section: Bone Scintigraphy Including Spect and Spect/ctmentioning
confidence: 99%
“…PET scans have limited resolutions, but fusion with CT (PET-CT) allows more precise localization of radiotracer uptake. While this modality is more sensitive and specific than SS, its role is controversial due to its increased radiation dose and high cost [27] . Currently it is only recommended if plain radiography, CT, SS, and MRI do not provide adequate information for diagnosis or treatment planning [24] .…”
Section: Treatment Modality and Tumor Evaluationmentioning
confidence: 99%